Centre and periphery within the borders of Islam proceedings of the 23rd congress of L'Union Europeenne des Arabisants et Islamisants - Contu, Giuseppe (Orientalia Lovaniensia Analecta, 2012)
This volume contains the Proceedings of the 23rd Congress of L'Union Europacuteeenne des Arabisants et Islamisants held in Sassari from Thursday 28th of September to Sunday 1st October 2006. The 26 articles contained in the Volume written by specialists from all over Europe (Russia, Finland, Poland, England, France, Italy, Spain, Germany, Portugal, Belgium and the Netherlands) deal with the following subjects: Islam, History, Society and Archaeology, Literature and Arabic Language and Linguistics. The Central Theme focuses on how the characteristics of Islam and Arabism are to be found in the periphery of the Arabic and Islamic world in relation to its Center and the interchanges implied by the geographic distance between center and periphery. The University of Sassari was the right ambiance for such a Congress since there was in the past some Arabic presence in Sardinia, which island was itself situated at the borders of the Islamic and Arabic Mediterranean.